Progressive Islamic Education at Muhammadiyah At-Tajdid Islamic Boarding School in Blora - Wahab, Ahmad; Abdul Haris; Syamsurizal Yazid (IJESS International Journal of Education and Social Science, 2025)
Since its establishment, Muhammadiyah has always focused on advancing education, resulting in numerous educational institutions across various levels as evidence of its dedication to enlightening the nation. However, despite its significant quantity, Muhammadiyah's quality is still considered mediocre, necessitating innovative ideas to achieve its goals. Progressive Islamic Education emerges as a solution to address the stagnation in Muhammadiyah's educational progress. This concept is Muhammadiyah's interpretation of K.H. Ahmad Dahlan's practical teachings. Progressive Islamic Education aims to shape students' personalities by integrating religious and general sciences to address real-life societal issues.This study aims to describe the concept and implementation of Progressive Islamic Education at Pondok Pesantren Muhammadiyah At-Tajdid Blora. Using a qualitative approach with a case study method, the researcher directly observed and interviewed individuals involved with the concept and implementation of Progressive Islamic Education at the pesantren, while also gathering data through documentation. The study's findings reveal that Pondok Pesantren Muhammadiyah At-Tajdid Blora formulates Progressive Islamic Education into several key points: aligning objectives with Muhammadiyah's goals, integrating religious and general educational content, emphasizing positive aspects in its methods, and conducting thorough evaluations. Its implementation occurs in three phases. The first phase instills Islamic values and knowledge to shape students' character. The second phase involves experiential learning through holiday activities, such as teaching at Al-Quran learning centers. The third phase places students in the community to solve problems using their acquired knowledge and experience.